(3eSCdI aj GNJdGa CbhGd GdYdeGA aj HbGA CLSGO GdCfHjGA aj bHhQges - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s
(3ChdgG (B:s
(3eSCdI aj GNJdGa CbhGd GdYdeGA aj HbGA CLSGO GdCfHjGA aj bHhQge aj GNJdGa GdCNHGQ hGdQhGjGJ(B...s
(3BNQgG (B:s
(3hHYHGQI GNQi(B: (3CLSGOge aj GdSeGA aj bHhQge hMaQge GdeYdheI (B... (3hUdi Gddg Ydi eMeO hBdg(B...s
(3jSHbgG cJGH(B: (3TQM GdahGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds